2019
DOI: 10.1007/s00394-019-02052-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of sitosterol and sitostanol on mitochondrial respiration in human brown adipocytes, myotubes and hepatocytes

Abstract: Purpose Lowering of LDL cholesterol levels by plant sterols and stanols is associated with decreased risk of cardiovascular disease in humans. Plant sterols and stanols also lower triacylglycerol (TG). However, it is not fully understood how reduction in TG is achieved and what the full potential of plant sterols and stanols is on whole-body metabolism. We here hypothesize that high levels of plant sterols and stanols stimulate whole-body energy expenditure, which can be attributed to changes in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…7 A–D). Similar to previous studies, we did not find direct effects or sufficiently significant differences (p < 0.05) of phytosterols on mitochondrial function under stress in normal cell culture conditions ( Nascimento et al, 2020 ). Although phytosterols are considered to be resistant to oxidative stress and lipid peroxidation via estrogen receptor mediated PI3K/GSK3 signaling ( Shi et al, 2013 ), and increasing mitochondrial membrane potential under stress conditions ( Wong et al, 2016 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…7 A–D). Similar to previous studies, we did not find direct effects or sufficiently significant differences (p < 0.05) of phytosterols on mitochondrial function under stress in normal cell culture conditions ( Nascimento et al, 2020 ). Although phytosterols are considered to be resistant to oxidative stress and lipid peroxidation via estrogen receptor mediated PI3K/GSK3 signaling ( Shi et al, 2013 ), and increasing mitochondrial membrane potential under stress conditions ( Wong et al, 2016 ).…”
Section: Resultssupporting
confidence: 91%
“…Although phytosterols are considered to be resistant to oxidative stress and lipid peroxidation via estrogen receptor mediated PI3K/GSK3 signaling ( Shi et al, 2013 ), and increasing mitochondrial membrane potential under stress conditions ( Wong et al, 2016 ). Interestingly, previous studies highly recommend that phytosterols have a better effect to the mitochondrial function in low glucose-containing medium ( Nascimento et al, 2020 ). Notably, protocatechuic acid ( Abdelmageed et al, 2021 ), sinapic acid ( Cherng et al, 2013 ), and vanillic acid ( Chang et al, 2015 ) are associated with hypoglycemia, which is considered one reason for the improvement of mitochondrial functional regulation by stigmasteryl phenolates.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, although only a few data are currently available, many investigations have suggested that mitochondria and oxidative stress constitute potential direct or indirect targets of phytosterols. In this context, sitostanol and sitosterol show beneficial effects on mitochondrial respiration in human hepatocytes, brown adipocytes, and myotubes [ 94 ]. Moreover, sitosterol has been shown to enhance mitochondrial ATP content and membrane potential in H9c2 cardiomyocytes [ 95 ].…”
Section: Phytosterols In Human Nutritionmentioning
confidence: 99%
“…The oxidation products of stigmasterol interfere with the female sex hormone 17β-estradiol in human breast and endometrial cells. [ 47 ] Stigmasterol Causes Ovarian Cancer Cell Apoptosis by Inducing Endoplasmic Reticulum and Mitochondrial Dysfunction. [ 48 ] Stigmasterol is also a potential metabolic regulator of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%